Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Section 10.7 - Complex Numbers - Exercise Set - Page 741: 101


$6-3i\sqrt 3$

Work Step by Step

$(8-\sqrt {-3})-(2+\sqrt {-12})$ =$(8-\sqrt {-1\times3})-(2+\sqrt {-1\times12})$ =$(8-\sqrt {-1}\sqrt 3)-(2+\sqrt {-1}\sqrt {12})$ =$(8-i\sqrt 3)-(2+i\sqrt {12})$ =$8-i\sqrt 3-2-i\sqrt {12}$ =$8-i\sqrt 3-2-i\sqrt {4\times3}$ =$8-i\sqrt 3-2-i\sqrt 4\sqrt 3$ =$8-2-i\sqrt 3-2i\sqrt 3$ =$6-3i\sqrt 3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.